2013
DOI: 10.1515/cclm-2012-0413
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide multicenter study aimed at the establishment of common reference intervals for standardized clinical laboratory tests in Japan

Abstract: Since no between-region variation was detected in reference values among accuracy-certified core laboratories, RIs applicable nationwide were established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 11 publications
1
20
1
Order By: Relevance
“…2.51 mmol/L, TG in female < 0.34 mmol/L, TG in female > 1.4 mmol/L, uric acid (UA) in male < 224 mmol/L, UA in male > 474 mmol/L, UA in female < 154 mmol/L, UA in male > 334 mmol/L, glucose (GLU) < 4.2 mmol/L, GLU > 5.9 mmol/L, γ-glutamyltransferase ≥ 100 U/L, alanine aminotransferase (ALT) < 8 U/L, ALT > 32 U/L, γ-glutamyltransferase (GT) < 9 U/L, GT > 55 U/L, creatine kinase (CK) < 61 U/L, CK > 257 U/L, C-reactive protein (CRP) > 1.4 mg/L, hemoglobin (Hb) in male < 135 g/L, Hb in male > 169 g/L, Hb in female < 110 g/L, Hb in female > 148 g/L, mean corpuscular volume (MCV) < 82 fl, MCV > 98 fl, in accordance with a previousreport of RIs in Japanese population 14. …”
supporting
confidence: 90%
“…2.51 mmol/L, TG in female < 0.34 mmol/L, TG in female > 1.4 mmol/L, uric acid (UA) in male < 224 mmol/L, UA in male > 474 mmol/L, UA in female < 154 mmol/L, UA in male > 334 mmol/L, glucose (GLU) < 4.2 mmol/L, GLU > 5.9 mmol/L, γ-glutamyltransferase ≥ 100 U/L, alanine aminotransferase (ALT) < 8 U/L, ALT > 32 U/L, γ-glutamyltransferase (GT) < 9 U/L, GT > 55 U/L, creatine kinase (CK) < 61 U/L, CK > 257 U/L, C-reactive protein (CRP) > 1.4 mg/L, hemoglobin (Hb) in male < 135 g/L, Hb in male > 169 g/L, Hb in female < 110 g/L, Hb in female > 148 g/L, mean corpuscular volume (MCV) < 82 fl, MCV > 98 fl, in accordance with a previousreport of RIs in Japanese population 14. …”
supporting
confidence: 90%
“…RIs established by a multicenter study were expected to become wider than those established by a single laboratory due to the inclusion of between-laboratory variation [23]. Yamamoto et al [23] recently established common RIs for standardized clinical laboratory tests in Japan by nationwide collaboration of more than 100 accuracycertified core laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…Yamamoto et al [23] recently established common RIs for standardized clinical laboratory tests in Japan by nationwide collaboration of more than 100 accuracycertified core laboratories. Although the reported RIs were close to those reported by Ichihara et al [24], it was necessary to adjust the dataset for unbalanced age and male/female ratios and to delete results from some laboratories which showed biases exceeding the allowable limits.…”
Section: Discussionmentioning
confidence: 99%
“…Ethical approval of the studies was obtained at each institution of the participating laboratories, and written informed consent was obtained from each volunteer as described in the respective reports. 1,3,4 The IFCC/APFCB and JAMT studies requested avoidance of strenuous physical exertion/exercise for the preceding four days and of excessive eating or drinking the night before; volunteers were asked to fast for at least 10 h prior to sampling. Venipuncture was performed between 7 and 10 AM, after the donor had been sitting quietly for at least 15 min to avoid variations of test results by posture and physical activity.…”
Section: Source Datamentioning
confidence: 99%
“…In the meanwhile, two other multicentre studies were conducted in Japan, one by a group of hospitals associated with Kyushu University (KU) 3 and the other by the Japanese Association of Medical Technologists (JAMT). 4 In the KU and JAMT studies, the specimens collected at each participating laboratory were measured locally, and the test results were combined following coordination of results using cross-check testing among the collaborating laboratories. Since the protocols used for recruitment of healthy individuals for the studies were found to be well harmonized, the Committee of Common Reference Intervals (C-CRI) of the Japan Society of Clinical Chemistry (JSCC) launched this project of merging the three datasets for establishment of reliable and reproducible nationwide RIs for 40 frequently tested analytes, most of which had been well standardized in Japan.…”
Section: Introductionmentioning
confidence: 99%